FACT and Ash1 promote long-range and bidirectional nucleosome eviction at the HO promoter - Yu, Yaxin (Nucleic Acids Res, 2020)
The Saccharomyces cerevisiae HO gene is a model regulatory system with complex transcriptional regulation. Budding yeast divide asymmetrically and HO is expressed only in mother cells where a nucleosome eviction cascade along the promoter during the cell cycle enables activation. HO expression in daughter cells is inhibited by high concentration of Ash1 in daughters. To understand how Ash1 represses transcription, we used a myo4 mutation which boosts Ash1 accumulation in both mothers and daughters and show that Ash1 inhibits promoter recruitment of SWI/SNF and Gcn5. We show Ash1 is also required for the efficient nucleosome repopulation that occurs after eviction, and the strongest effects of Ash1 are seen when Ash1 has been degraded and at promoter locations distant from where Ash1 bound. Additionally, we defined a specific nucleosome/nucleosome-depleted region structure that restricts HO activation to one of two paralogous DNA-binding factors. We also show that nucleosome eviction occurs bidirectionally over a large distance. Significantly, eviction of the more distant nucleosomes is dependent upon the FACT histone chaperone, and FACT is recruited to these regions when eviction is beginning. These last observations, along with ChIP experiments involving the SBF factor, suggest a long-distance loop transiently forms at the HO promoter.